2009
DOI: 10.1128/aem.02453-08
|View full text |Cite
|
Sign up to set email alerts
|

A Vaccine against Rumen Methanogens Can Alter the Composition of Archaeal Populations

Abstract: The objectives of this study were to formulate a vaccine based upon the different species/strains of methanogens present in sheep intended to be immunized and to determine if a targeted vaccine could be used to decrease the methane output of the sheep. Two 16S rRNA gene libraries were used to survey the methanogenic archaea in sheep prior to vaccination, and methanogens representing five phylotypes were found to account for >52% of the different species/strains of methanogens detected. A vaccine based on a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 25 publications
8
74
1
2
Order By: Relevance
“…However, the rumen methanogens present in sheep from Venezuela had 19.2 % of all clones with 99 % similarity to M. thaueri and had 39.4 % (41/104) of clones with 97.9-98.5 % identity to Methanobrevibacter gottschalkii [42]. The absence of M. thaueri-related sequences was observed in alpacas from Vermont, water buffalo on three different diets, sheep in Western Australia, sheep from Queensland, Australia, and in Sika deer from China [26,34,41,43,47]. Comparing the methanogen diversities of previous studies to the present study suggests that both the diet of the impala and the unknown factors in the rumen allow for M. thaueri-like methanogens to thrive over other methanogen species.…”
Section: Impala Rumen Methanogens In Relation To Domestic and Wild Rumentioning
confidence: 96%
“…However, the rumen methanogens present in sheep from Venezuela had 19.2 % of all clones with 99 % similarity to M. thaueri and had 39.4 % (41/104) of clones with 97.9-98.5 % identity to Methanobrevibacter gottschalkii [42]. The absence of M. thaueri-related sequences was observed in alpacas from Vermont, water buffalo on three different diets, sheep in Western Australia, sheep from Queensland, Australia, and in Sika deer from China [26,34,41,43,47]. Comparing the methanogen diversities of previous studies to the present study suggests that both the diet of the impala and the unknown factors in the rumen allow for M. thaueri-like methanogens to thrive over other methanogen species.…”
Section: Impala Rumen Methanogens In Relation To Domestic and Wild Rumentioning
confidence: 96%
“…A similar vaccine was used in a New Zealand study, but in that trial there was no significant reduction in methane emissions (Leslie et al, 2008). The authors of the initial Australian study subsequently discovered that ,20% of the different species of methanogens detected in the sheep were closely related to the methanogen strains used in the vaccine (Wright et al, 2006;Williams et al, 2009). A further vaccination trial was conducted in sheep using a more targeted vaccine based on the different species of methanogens found to be present in the animals (Williams et al, 2009).…”
Section: Vaccines Targeting S Bovis and Lactobacillusmentioning
confidence: 99%
“…Although the negative association between Entodinium spp. and CH 4 and CH 4 GEI was surprising given that these hydrogen producers are deemed to positively influence CH 4 production, it has also been reported that methanogens take longer than other rumen microbes to adapt to changes in their environment (57). Further-more, methanogenesis could potentially be altered due to fluctuations in the abundances of other H 2 -producing rumen microbes.…”
Section: Figmentioning
confidence: 99%